Interlingual Subtitles to Increase High School Students’ Ability in Understanding Explanation Texts - Ikke Dewi Pratama; Woro Retnaningsih; Muhammad Romdhoni Prakoso (Metathesis: Journal of English Language, Literature, and Teaching, 2021)
This paper explores the use of interlingual subtitle as a media in teaching reading skill in one of private high schools in Surakarta. This research was initially conducted as the teachers found problems in teaching genres of texts, especially explanation text. Interlingual subtitle which is placed in videos is offered by the researchers as a solution and expected to help students in understanding the content of explanation text. This research uses classroom action research method with two cycles. The objectives of this research are to find out: 1) the implementation of interlingual subtitle in teaching explanation text, and 2) the impacts of interlingual subtitle on students’s achivements. The subjects of this research are 33 students of social science class and 33 students of natural science class. It is found out that interlingual subtitle can be used as a supplementary material in teaching explanation text. Interlingual subtitle has also contributed positively to the increasing scores of the students during the pre-test to the post-test.